Development of a test to measure teachers' competence in methods and end-product of inquiry in environmental science I - Valencia, Irene (Nazario)
The development of a test instrument, the Science Test of Inquiry, is proposed in this study to measure teacher's competence in methods and end-product of inquiry, specifically, in the use of Environmental Science I, a UP-SEC curriculum material for a first year science course. Specific processes were considered to comprise the methods of inquiry: searching, processing of data, discovering a possible solution, and verification of the answer. The end-product of inquiry is the application of discovered and verified concepts to new problem situations.